The effect of crystal orientation on the cryogenic strength of hydroxide catalysis bonded sapphire. (17th March 2015) - Haughian, K; Douglas, R; Veggel, A A van; Hough, J; Khalaidovski, A; Rowan, S; Suzuki, T; Yamamoto, K
Abstract: Hydroxide catalysis bonding has been used in gravitational wave detectors to precisely and securely join components of quasi-monolithic silica suspensions. Plans to operate future detectors at cryogenic temperatures has created the need for a change in the test mass and suspension material. Mono-crystalline sapphire is one candidate material for use at cryogenic temperatures and is being investigated for use in the KAGRA detector. The crystalline structure of sapphire may influence the properties of the hydroxide catalysis bond formed. Here, results are presented of studies of the potential influence of the crystal orientation of sapphire on the shear strength of the hydroxide catalysis bonds formed between sapphire samples. The strength was tested at approximately 8 K; this is the first measurement of the strength of such bonds between sapphire at such reduced temperatures. Our results suggest that all orientation combinations investigated produce bonds of sufficient strength for use in typical mirror suspension designs, with average strengths >23 MPa.